ANALYSIS OF THE PROMOTION OF NEW STUDENT ADMISSIONS FROM THE PERSPECTIVE OF ISLAMIC BUSINESS ETHICS - Gusti Oka Widana; Zainal Potton; Supriyandi Supriyandi (SEAN Institute, 2023)
The objective of this research is to uncover how the promotion activity of Universitas Muhammadiyah Enrekang in South Sulawesi Province is implemented according to Islamic business ethics to recruit new students. This research uses qualitative methods, namely by structured interviews with the Promotion Department of Universitas Muhammadiyah Enrekang, in June-August 2022. This research found that Universitas Muhammadiyah Enrekang uses a promotion model that is complied with the Islamic business ethics, which consists of of autonomy, honesty, justice, mutual benefit and moral integrity. This research also reveals that these promotional activities are not merely business activities but have da'wah values. The novelty of this research is in describing how promotion can be done in line with the principles of Islamic business ethics and how business and ethics are two things that be able to in line.